Timing of Pediatric Palliative Care Consults in Hospitalized Patients with Heart Disease - Green, Danielle J.; Bennett, Erin; Olson, Lenora M.; Wawrzynski, Sarah; Bodily, Stephanie; Moore, Dominic; Mansfield, Kelly J.; Wilkins, Victoria; Cook, Lawrence; Delgado-Corcoran, Claudia (Journal of Pediatric Intensive Care, 2021)
Pediatric palliative care (PPC) provides an extra layer of support for families caring for a child with complex heart disease as these patients often experience lifelong morbidities with frequent hospitalizations and risk of early mortality. PPC referral at the time of heart disease diagnosis provides early involvement in the disease trajectory, allowing PPC teams to longitudinally support patients and families with symptom management, complex medical decision-making, and advanced care planning. We analyzed 113 hospitalized pediatric patients with a primary diagnosis of heart disease and a PPC consult to identify timing of first PPC consultation in relation to diagnosis, complex chronic conditions (CCC), and death. The median age of heart disease diagnosis was 0 days with a median of two CCCs while PPC consultation did not occur until a median age of 77 days with a median of four CCCs. Median time between PPC consult and death was 33 days (interquartile range: 7–128). Death often occurred in the intensive care unit (n = 36, 67%), and the most common mode was withdrawal of life-sustaining therapies (n = 31, 57%). PPC referral often occurred in the context of medical complexity and prolonged hospitalization. Referral close to the time of heart disease diagnosis would allow patients and families to fully utilize PPC benefits that exist outside of end-of-life care and may influence the mode and location of death. PPC consultation should be considered at the time of heart disease diagnosis, especially in neonates and infants with CCCs.
Keywords: palliative care; pediatrics; heart diseases; hospitalized child; advance care planning